Cantinas coloniais e o vinho português na capital de Moçambique - Domingos, Nuno (Trabalhos de Antropologia e Etnologia, 2020)
This article aims to interpret the links between the Portuguese wine trade towards the colonial territories and the network of relations that, in the terrain, involved this traffic. In this context, the canteens, places where de metropolitan wine was sold in the colony of Mozambique, are privileged observatories of research. Based on a secondary bibliography, but also on the results from fieldwork conducted in Maputo, this text poses a set of research questions directed to the so-called late colonial period, when the Portuguese colonies, namely Angola and Mozambique, became the main destination of the metropolitan table wine.